The extent to which physical activity contributes to the formation of healthy behaviors to avoid sports injuries: A field study among secondary school students in the province of Souk Ahras. - belboul, moussa (sports creativity, 2025)
No one denies the role that physical activity plays in an individual’s social, mental, psychological and health life, and this has been shown by several extensive studies. Perhaps the positive aspect is of great importance and every individual seeks to elevate it to the highest levels in all ways and means. Physical activity and sports have contributed positively and remarkably to the development and maintenance of health through modern training methods and techniques that aim to prevent or reduce sports injuries. These methods take into account several priorities surrounding the individual, such as the intensity of the training load and the conditions associated with it. Among the important health aspects that every individual strives to support and maintain are healthy behaviors. These behaviors refer to all patterns of conduct aimed at developing and enhancing an individual's health capabilities. These behaviors may lead to the formation of optimal health, meaning a state of complete physical, mental, and social well-being and efficiency, and not merely the absence of disease and infirmity, as defined by the World Health Organization (WHO). Our study will focus on a group of secondary school students who engage in physical activity and sports within the school, or possibly outside of it. This will be done through a descriptive approach using a questionnaire to assess specific health behaviors and sports injuries.